The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1034/j.1399-3038.2003.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose theophylline in childhood asthma: a placebo‐controlled, double‐blind study

Abstract: Regular anti-inflammatory treatment is essential in treating persistent asthma. Most commonly, inhaled corticosteroids (ICS) are used. However, especially in children, there is concern about the long-term safety of ICS such that doses should be kept to a minimum. The use of theophylline has decreased because of frequent side-effects in therapeutic doses. In adults, there have been reports about an immunomodulatory effect of low-dose theophylline. To study the clinical and immunomodulatory effect in children, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Theophylline, although effective is considered as the third-line therapy in the treatment of bronchial asthma due to the drug's frequent side effects. The low-dose of theophylline in moderate childhood asthma is safe and well tolerated (Suessmuth, 2003). At low doses, the drug is easier to use, side effects are uncommon and the problems of drug interaction are less of an issue, thus making the clinical use of theophylline less complicated.…”
Section: Obstructive Airway Diseasesmentioning
confidence: 99%
“…Theophylline, although effective is considered as the third-line therapy in the treatment of bronchial asthma due to the drug's frequent side effects. The low-dose of theophylline in moderate childhood asthma is safe and well tolerated (Suessmuth, 2003). At low doses, the drug is easier to use, side effects are uncommon and the problems of drug interaction are less of an issue, thus making the clinical use of theophylline less complicated.…”
Section: Obstructive Airway Diseasesmentioning
confidence: 99%
“…70, 71 One small trial showed that the addition of theophylline to inhaled corticosteroids resulted in improvement in peak expiratory flow, but did not improve FEV1 or bronchial reactivity. 72 Given the lack of substantial supporting evidence, potential toxicity, and need for frequent monitoring, theophylline is not part of first-line therapy for children with asthma and is not recommended for children under 5. 5 …”
Section: Alternatives To Inhaled Corticosteroidsmentioning
confidence: 99%